The Complete Chloroplast Genomes of Echinacanthus Species (Acanthaceae): Phylogenetic Relationships, Adaptive Evolution, and Screening of Molecular Markers - Gao, Chunming; Deng, Yunfei; Wang, Jun (Frontiers in Plant Science, 2019)
Among the four species of Echinacanthus (Acanthaceae), one distributed in the West Himalayan region and three restricted to the Sino-Vietnamese karst region. Because of its ecological significance, molecular markers are necessary for proper assessment of its genetic diversity and phylogenetic relationships. Herein, the complete chloroplast genomes of four Echinacanthus species were determined for the first time. The results indicated that all the chloroplast genomes were mapped as a circular structure and each genomes included 113 unique genes, of which 80 were protein-coding, 29 were tRNAs, and 4 were rRNAs. However, the four cp genomes ranged from 151,333 to 152,672 bp in length. Comparison of the four cp genomes showed that the divergence level was greater between geographic groups. We also analyzed IR expansion or contraction in the four cp genomes and the fifth type of the large single copy/inverted repeat region in Lamiales was suggested. Furthermore, based on the analyses of comparison and nucleotide variability, six most divergent sequences (rrn16, ycf1, ndhA, rps16-trnQ-UUG, trnS-GCU-trnG-UCC, and psaA-ycf3) were identified. A total of 37-45 simple sequence repeats were discovered in the four species and 22 SSRs were identified as candidate effective molecular markers for detecting interspecies polymorphisms. These SSRs and hotspot regions could be used as potential molecular markers for future study. Phylogenetic analysis based on Bayesian and parsimony methods did not support the monophyly of Echinacanthus. The phylogenetic relationships among the four species were clearly resolved and the results supported the recognition of the Sino-Vietnamese Echinacanthus species as a new genus. Based on the protein sequence evolution analysis, twelve genes (rpl14, rpl16, rps4, rps15, rps18, rps19, psbK, psbN, ndhC, ndhJ, rpoB, and infA) were detected under positive selection in branch of Sino-Vietnamese Echinacanthus species. These genes will lead to understanding the adaptation of Echinacanthus species to karst environment. The study will help to resolve the phylogenetic relationship and understand the adaptive evolution of Echinacanthus. It will also provide genomic resources and potential markers suitable for future species identification and speciation studies of the genus.